THE QUR'AN AS A HOLY TEXT: RECONSTRUCTION OF REVELATION AND PROPHETIC IDENTITY - Zulkarnaini, Zulkarnaini (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
The relationship between revelation and Prophethood is the essence of the Qur'an studies, but this theme has yet to receive serious attention from the Qur'an and commentary studies. This article reviews the concept of revelation and prophecy from a critical perspective. As a holy book considered sacred, the Qur'an faces rational challenges that need to be responded to scientifically. This study uses a qualitative method with a literature study approach. The researcher collects various literature related to the research theme, then analyzes it critically. The research findings show that the attitude of faith that believes in the truth of the Qur'an without being accompanied by scientific arguments does not make the sacredness of the Qur'an properly treated because every dimension of belief requires the support of scientific argumentation in the context of an increasingly advanced civilization. As a sacred text, The Qur'an must be reviewed critically to provide a scientific dimension, especially regarding the relationship between prophecy and revelation. The existence of the Prophet as the bearer of revelation has received challenges from some communities because humanity has difficulty balancing its physical and spiritual dimensions. Humans, as physical and spiritual beings, need a scientific and rational perspective in caring for faith, especially regarding the relationship between prophecy and revelation, which is part of the Islamic discourse that has taken place throughout the history of Muslim civilization.